Hi5 : arise from the ashes? - Oelrich, Nikki, (SAGE Knowledge. Cases., 2017)
Stimulated by social injustice, the Dutch foundation Hi5 aimed to change the way businesses and young people think and act: Businesses have too many prejudices, which limit them from tapping into the talent pool, whereas youngsters play the victim too much, as they believe they cannot achieve great things due to their background, age or religion. In May 2013, five years after its founding, Hi5's performance was beyond expectations and the brand name became well known. At the peak of its success, however, Hi5 could not continue using the brand name due to legal complications. The success also had an immense impact on the private lives of Hi5 employees who were all near 30 - their salaries were modest and the work-life balance was out of sync. The 26-year old founder, Dionne Abdoelhafiezkhan, needed to make an urgent decision whether to discontinue Hi5 or to make an entrepreneurial restart with a new brand name.